THE ROLE AND SIGNIFICANCE OF LASER THERAPY IN GYNECOLOGY (American Journal of Technology and Applied Sciences, 2026)
This article provides an evidence-based analysis of the application of laser therapy in gynecology, including its effectiveness, advantages, and limitations. The effects of laser radiation on pathological tissues, prevention of bleeding, acceleration of tissue regeneration, minimal invasiveness, and reduction of rehabilitation time are described in detail. The article also provides comprehensive information on the use of laser therapy in cervical uterine diseases, tumor-like lesions associated with human papillomavirus, atrophic changes during menopause, and stress urinary incontinence.